Performance and plasma concentration of metabolites in transition dairy cows supplemented with vitamin E and fat - Rohollah Amirifard; Mohammad Khorvash; Masiholla Forouzmand; Hamid-Reza Rahmani; Ahmad Riasi; Mohammad Malekkhahi; Mojtaba Yari; Morteza Hosseini-Ghaffari (Journal of Integrative Agriculture, 2016)
The objective of this study was to evaluate the effects of vitamin E (VE; 1 500 or 3 000 international units (IU) d−1) and fat (2% of dry matter calcium salt of soybean oil) supplementation during the transition period on feed intake, milk yield and composition and blood metabolites of dairy cows. 48 multiparous Holstein cows were randomly assigned into one of four treatments in a 2×2 factorial arrangement of vitamin E and supplemental dietary fat during the transition period. Treatments were: 1) 1 500 IU d−1 vitamin E without fat supplementation (1 500VE–F); 2) 1 500 IU d−1 vitamin E with fat supplement (1 500VE+F); 3) 3 000 IU d−1 vitamin E without fat supplementation (3 000VE–F); and 4) 3 000 IU d−1 vitamin E with fat supplement (3 000VE+F). Dietary treatments were initiated at approximately 28 d before expected calving dates and continued through 28 d postpartum. Dry matter intake (DMI) was unaffected (P>0.05) by prepartum treatment. Regardless of vitamin E supplementation, DMI was greater (P<0.01) in fat-supplemented cows compared with un-supplemented cows (19.60 vs. 18.45 kg d−1; SEM=0.42) during the postpartum period. Energy balance and body weight were not affected (P>0.05) by treatments. Postpartum diets had no significant effect on milk yield or milk composition. Plasma concentrations of non-esterified fatty acids, glucose, and insulin were not affected (P>0.05) by treatments. Regardless of vitamin E supplementation, plasma β-hydroxybutyrate concentration was greater (P<0.05) in fat-supplemented cows compared with un-supplemented cows during the postpartum period. These results showed no indication of positive effects on lactation performance associated with vitamin E and dietary fat supplement in transition cows.